A simple method to suppress turbulence-induced multiple filamentation. (8th March 2019) - Zeng, Tao; Yang, Ming Ya
Abstract: In this study, we investigated several statistical parameters of laser filaments propagating in turbulent air using a lens or an axicon as the focusing optics. The results indicate that using an axicon with a relatively large bottom angle is an effective method to suppress turbulence-induced multiple filamentation. Our findings are valuable for subtle experiments, or many foreseen applications relying on a single steady laser filament propagating in turbulent air.